BEHAVIORAL BIAS (AVAILABILITY, REPRESENTATIVENESS, ANCHORING, AND CONFIRMATION) TOWARD INVESTMENT DECISION-MAKING - R, Mardiana; Yossinomita, Yossinomita; Saputra, M Haris; R, Mandasari; Kartika, Yulia D (Universitas Nusa Cendana, 2025)
When making investment decisions, retail investors tend to rely on shortcuts in thinking to process the information and data they get. This creates illogical thinking based on emotions or momentary judgments that can result in less-than-optimal investment performance and even losses. This research investigates the relationship between behavioral financial biases (like availability, representativeness, anchoring, and confirmation) and investment decision-making. This study method uses purposive sampling with certain characteristics. Data was collected from 130 retail investors for 3 months in 2024 and analyzed with SPSS Statistics. The research results show that confirmation bias and representativeness bias positively affect investment decision-making. However, anchoring bias and availability bias do not significantly affect investment decision-making. In addition, confirmation bias, representativeness bias, anchoring bias, and availability bias simultaneously positively affect investment decision-making. Financial behavioral biases that can influence investors are confirmation bias and representativeness bias, where retail investors tend to look for information according to their views and similarities based on certain stereotypes, which can reduce or cause losses in stock investments. Keywords: Anchoring Bias; Availability Bias; Confirmation Bias; Representativeness Bias; Investment Decision-Making